Role of neutrophil to lymphocyte ratio in prediction of acute exacerbation of chronic obstructive pulmonary disease - Aida M. Yousef; Wael Alkhiary (Egyptian Journal of Chest Disease and Tuberculosis, 2017)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease of the lung. Some of the inflammatory markers such as C-reactive protein (CRP), leukocyte count are associated with COPD. The aim of this study is to evaluate the role of neutrophil-to-lymphocyte ratio (NLR) as new inflammatory marker in COPD patients in comparison with the other well-known inflammatory markers. We prospectively evaluated neutrophil-to-lymphocyte ratio, CRP and ESR in 60 patients with stable COPD and 68 COPD patients during acute exacerbation and 60 sex- and age-matched healthy controls. We found that NLR values during acute exacerbation of the disease were significantly higher than those during stable period (P < 0.001). NRL values of the stable COPD patients were significantly higher than those of the controls (P < 0.001). NLR values were also positively correlated with serum CRP levels, ESR, and WBC. Conclusion: NLR can be used as a new inflammatory marker for assessment of inflammation in COPD patients. It is a good predictor for exacerbation of COPD. It is a quick, cheap, easily measurable marker with no need for a special request.